Melatonin and its analogs inhibit the basal and stimulated release of hypothalamic vasopressin and oxytocin in vitro. - Yasin, SA; Costa, A; Besser, G; Hucks, D; Grossman, A; Forsling, M (1993)
The secretion of neurohypophyseal hormone and ACTH in the rat has been shown to exhibit circadian rhythms, with high values during the day and low values throughout the night. The neurohypophyseal hormone daily rhythm is altered by exposure to constant light and by pinealectomy. It was, thus, proposed that the observed fall in vasopressin (AVP), oxytocin, and ACTH over the hours of darkness could be related to the release of melatonin seen at this time. Therefore, a study was performed to determine the effect of melatonin on AVP, oxytocin, and CRH-41 release from the isolated rat hypothalamus in vitro. Employing a previously validated technique, rat hypothalami were incubated in either medium alone or medium containing melatonin or one of two melatonin analogs. Hormone release was measured by RIA, and the ratios were calculated and compared by Student's t test, with Dunnett's correction for multiple comparisons. Melatonin showed a dose-dependent inhibition of both basal and stimulated AVP and oxytocin release in the concentration range 4.3 x 10(-10) to 2.5 x 10(-3) M, while having no significant effect on the release of CRH-41. The two melatonin analogs, 2-iodomelatonin and 5-methoxy-N-isobutanoyltryptamine, were also found to inhibit both basal AVP and oxytocin release, indicating that this effect probably depends upon the presence of melatonin receptors in the hypothalamus. This inhibitory modulation of AVP, in the absence of any effect on CRH-41, suggests that melatonin may affect water balance by means of directly inhibiting hypothalamic AVP release. Furthermore, circadian rhythmicity in pituitary-adrenal activity may depend on melatonin modulation of AVP, rather than changes in CRH-41.